(untitled) (Innovative professional education, 2025)
The article deals with the methods and technologies of forming the professional competence of future mechanics in vocational education institutions. The influence of pedagogical conditions, in particular internships, the use of cloud services, case methods and psychological support, on the development of motivational, cognitive, active and reflective components of competence is analyzed. The integration of modern educational technologies is proposed to improve the quality of training and competitiveness of specialists